Malihi sebagai Ide Dasar Penciptaan Tari Kreasi - Khatarina, Febya; Astuti, Andi Arie; Romadoni, Muhamad (Tambuleng, 2025)
The preservation of Dayak Ngaju culture in Central Kalimantan is a strategic effort to protect ancestral heritage from the erosion caused by modernization and globalization. The Dayak Ngaju culture is rich in traditional ceremonies, dance arts, traditional music, local language, and indigenous values that reflect a harmonious relationship between humans, nature, and spirituality. The creation of the Malihi dance aims to preserve these cultural values through a tradition-based performing arts approach. The method used in the creative process is an artistic creation method, which includes stages of exploration, design, and realization. The creation of the Malihi dance seeks to preserve Dayak Ngaju culture through an innovative and creative performing arts approach. This work highlights the richness of local culture through traditional movement patterns, costumes, and music, which are then combined with contemporary dance elements to remain relevant in today’s performing arts context. The Malihi dance functions not only as a medium of artistic expression but also as a communicative means of cultural preservation and a way to introduce Dayak Ngaju values to broader audiences. For the creator, this work also serves as a means of personal development, academic fulfillment, and a strategic contribution to safeguarding cultural heritage that deserves support and appreciation.